Very high-frequency oscillations: Novel biomarkers of the epileptogenic zone - Brázdil, Milan; Pail, Martin; Halámek, Josef; Plešinger, Filip; Cimbálník, Jan; Roman, Robert; Klimeš, Petr; Daniel, Pavel; Chrastina, Jan; Brichtová, Eva; Rektor, Ivan; Worrell, Gregory A; et al. (Annals of neurology, 2017)
OBJECTIVE: In the present study, we aimed to investigate depth electroencephalographic (EEG) recordings in a large cohort of patients with drug-resistant epilepsy and to focus on interictal very high-frequency oscillations (VHFOs) between 500Hz and 2kHz. We hypothesized that interictal VHFOs are more specific biomarkers for epileptogenic zone compared to traditional HFOs. METHODS: Forty patients with focal epilepsy who underwent presurgical stereo-EEG (SEEG) were included in the study. SEEG data were recorded with a sampling rate of 25kHz, and a 30-minute resting period was analyzed for each patient. Ten patients met selected criteria for analyses of correlations with surgical outcome: detection of interictal ripples (Rs), fast ripples (FRs), and VHFOs; resective surgery; and at least 1 year of postoperative follow-up. Using power envelope computation and visual inspection of power distribution matrixes, electrode contacts with HFOs and VHFOs were detected and analyzed. RESULTS: Interictal very fast ripples (VFRs; 500-1,000Hz) were detected in 23 of 40 patients and ultrafast ripples (UFRs; 1,000-2,000Hz) in almost half of investigated subjects (n = 19). VFRs and UFRs were observed only in patients with temporal lobe epilepsy and were recorded exclusively from mesiotemporal structures. The UFRs were more spatially restricted in the brain than lower-frequency HFOs. When compared to R oscillations, significantly better outcomes were observed in patients with a higher percentage of removed contacts containing FRs, VFRs, and UFRs. INTERPRETATION: Interictal VHFOs are relatively frequent abnormal phenomena in patients with epilepsy, and appear to be more specific biomarkers for epileptogenic zone when compared to traditional HFOs. Ann Neurol 2017;82:299-310.
Keywords: mozkové vlny; Electroencephalography; Male; Brain Waves; elektroencefalografie; Adult; dospělí; mužské pohlaví; epilepsie parciální; Endophenotypes; lidé; ženské pohlaví; Humans; Drug Resistant Epilepsy; Epilepsies, Partial; refrakterní epilepsie; endofenotypy; Female; lidé středního věku; Middle Aged